Working with Chinese Olympic athletes in their national sport system: From the conceptual to a proposed research-practice integration - Ge, Y.; Schinke, R.; Dong, D.; Lu, C.; Si, G.; Oghene, O. (International Journal of Sport and Exercise Psychology, 2019)
In order to reveal the socio-cultural environment`s impact upon Chinese athletes careers, the authors discuss the characteristics of the Chinese sport system (termed the Chinese Whole-Nation system) and within it, the related experiences of two successful Chinese Olympic athletes who developed in this system. From the perspectives of the two Chinese Olympic champions and the academic authors, the Chinese Whole-Nation system is summarised as having the following characteristics: (a) a centralised structure, (b) a medal-orientated, and (c) a semi-closed environment. Within the Chinese Whole-Nation system, elite athletes experience the psychological issues of growth of autonomy, medal-orientation pressure, and career transition crises. Derived from these three issues, the authors propose that in the Chinese national sport context, facilitating the relationships, dialectic thinking cultivation, and balancing the athletes` and collective interests should be the focus for sport psychology practitioners. In relation to the broader discussion of this national sport system, the scholars then propose research topics and a methodological approach through which to engage in culturally safe research that can augment practice.